The common regulatory pathway of COVID-19 and multiple inflammatory diseases and the molecular mechanism of cepharanthine in the treatment of COVID-19 - Jiang, Ping; Ye, Jingyao; Jia, Menglong; Li, Xiaopeng; Wei, Shujun; Li, Nianhu (Frontiers in Pharmacology, 2022)
Background: Similar pathogenesis makes COVID-19 associated with RA, AS and GA, and it is possible to introduce common drugs for the treatment of RA, AS and GA into the treatment of COVID-19. That is, "homotherapy for heteropathy", especially cytokine inhibitors. In addition, "new use of old drugs" is an important short-term strategy for the treatment of COVID-19. Cepharanthine is mainly used in the treatment of leukopenia and has recently been proved to have a good therapeutic effect on COVID-19, but its specific molecular mechanism has not been clearly explained. The purpose of this work is to explore the common targets and signaling pathways among COVID-19, RA, AS and GA by means of network pharmacology (NP), and to infer the potential mechanism of CEP in the treatment of COVID-19. Methods: Firstly, SwissTargetPrediction was used to predict the targets of CEP, and the pathogenic targets of COVID-19, RA, AS and GA were searched in GeneCards database and literature, respectively. Then, the protein interaction network of CEP and COVID-19 cross targets and the common targets of COVID-19, RA, AS and GA was constructed. Cytosscape 3.7.2 software was used to construct CEP-common targets-signaling pathways-COVID-19 network, module function analysis, GO and KEGG. Finally, the molecular docking of hub targets and CEP was carried out by AutoDock software. Results: The results showed that the common targets of the four diseases were TNF, interleukin (IL)-6 and IL-1B, and the common signaling pathways were Coronavirus disease, IL-17 signaling pathway and TNF signaling pathway. CEP has a good binding force with AKT1, PIK3CA, PIK3CD and ACE2, and plays a role in the treatment of COVID-19 by regulating PI3K-Akt signaling pathway, Relaxin signaling pathway, VEGF signaling pathway and HIF-1 signaling pathway. Conclusion: Therefore, this study not only confirmed the potential mechanism of CEP in the treatment of COVID-19 at the molecular level, but also found that TNF and IL-17 inhibitors, which are commonly used in the treatment of RA, AS and GA, may also affect the treatment of COVID-19, which provides new clues and theoretical basis for the rapid discovery of effective therapeutic drugs for COVID-19.